Perencanaan Sistem Penyediaan Air Bersih di Desa Teluk Melano Kecamatan Simpang Hilir Kabupaten Kayong Utara - Susanti, Fitria; Utomo, Kiki Prio; Pramadita, Suci (Jurnal Teknologi Lingkungan Lahan Basah, 2024)
The lack of access to clean water services had led a significant portion of the community in Teluk Melano Village to rely on river water and rainwater as their primary sources to meet their needs. Teluk Melano Village has the highest population in the Simpang Hilir District, Kayong Utara Regency. As of now, Teluk Melano Village does not have a Clean Water Supply System (BPAM). Therefore, a study was needed to meet the demand for clean water by conducting a Clean WaterTreatment Plant (IPA Bersih) Planning for Teluk Melano Village. This study aimed to design a clean water supply system with a planning period of the next 15 years (2023-2037). The method used involved primary data collection based on SNI 6989.57.2008 and SNI 8066:2015, and secondary data collection sourced from the Teluk Melano Village Monograph for the years 2020 and 2022. The total demand for clean water in Teluk Melano Village in 2037 would be 3.39 liters/second with a population of 1930 people. The results of the water quality test of the Melani River in this study showed that the parameters of E-coli, color, and pH, based on Government Regulation No. 22 of 2021, Class1, on the Implementation and Management of the Environment, did not meet the standard quality requirements for clean water. The planned Water Treatment Plant (WTP) included a complete conventional treatment process, including coagulation using hydraulic type rapid mixing utilizing gravity on the waterfall, flocculation using vertical baffled channels, sedimentation using plate settlers to reduce turbidity, filtration using rapid sand filters with filter media consisting of quartz sand and support media consisting of gravel, disinfection using chemical disinfectant in the form of chlorine solution, neutralization using a dosing pump for the addition of lime, and the type of reservoir used is a ground reservoir.Keywords: clean water, Water Treatment Plant, Teluk Melano Village